Reinterpretation of The Cause of “Fasad” in QS. Ar-Rum: 41 Perspective of Noam Chomsky's Transformative Generative Theory - Mush’ab Wafi ‘Adalah (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
A correct understanding of the Qur'anic text has an important role in creating a good. This article aims to reinterpret the Qur'anic verses that are often used as the basis for the spirit of ecology but forget the most important things contained in it. This effort is important because of the position of the Qur'an as the first source in the foundation of Islamic law (the first resource) and being a sacred text that has an ecological spirit from the beginning of its revelation until the last day. This study uses the transformative generative theory carried by Noam Chomsky which underlines that in understanding a text can use an approach that is divided into two: first, deep structure or deep structure and second, surface structure. In understanding QS. Ar-Rum: 41, Samarqhandi, Fakhruddin Ar-Rozi and Ibn Kathir have almost the same interpretation narrative but have different wording in terms of replacement, expansion and addition and use more of a deep structure approach. While Ash-Sha'rawi and Thanthawi Jauhari both do not have similar interpretative narratives. Asy-Sya'rawi uses more of a surface structure approach. While Thantawi Jauhari uses more surface and deep structure. This article concludes that the cause of "fasad" is not only the lack of maintaining the spirit of ecology such as negligence, turning away and indifference in protecting the environment and exceeding the limits in doing damage as a result of the destruction of the environment.